Exterior material for all-solid-state battery, its manufacturing method, and all-solid-state battery

The laminate structure with a buffer layer outside the thermally fusion resin layer in the exterior material for all-solid-state batteries ensures uniform pressure distribution, addressing the issue of uneven restraint and peeling, and enhancing the battery's weight reduction and shape diversity.

JP7647547B2Active Publication Date: 2025-03-18DAI NIPPON PRINTING CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021505151
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-12
Filing Date
2020-03-12
Publication Date
2025-03-18
Estimated Expiration
2040-03-12

AI Technical Summary

Technical Problem

Existing exterior materials for all solid-state batteries face challenges in achieving uniform pressure distribution during high-pressure pressing, leading to uneven restraint and potential peeling between the solid electrolyte and active material layers.

Method used

A laminate structure for the exterior material, comprising a substrate layer, a barrier layer, and a thermally fusion resin layer, with an additional buffer layer outside the thermally fusion resin layer, functions as a pressure buffer to ensure uniform pressing on the press surface of the all-solid-state battery.

Benefits of technology

The proposed solution allows for uniform pressing on the press surface of all-solid-state batteries, effectively preventing peeling between the solid electrolyte and active material layers, and enabling the production of batteries with improved weight reduction and shape diversity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647547000006
    Figure 0007647547000006
  • Figure 0007647547000007
    Figure 0007647547000007
  • Figure 0007647547000008
    Figure 0007647547000008
Patent Text Reader

Abstract

An outer package material for all-solid-state batteries, which is composed of a multilayer body that is sequentially provided, from the outer side, with at least a base material layer, a barrier layer and a thermally fusible resin layer in this order, and which is configured such that the multilayer body has a layer that has a buffering function on the outer side of the thermally fusible resin layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an exterior material for an all-solid-state battery, a manufacturing method thereof, and an all-solid-state battery. [Background technology]

[0002] All-solid-state batteries, which use a solid electrolyte, are known. Since they do not use organic solvents, they have the advantages of being highly safe and having a wide operating temperature range.

[0003] On the other hand, it is known that all-solid-state batteries are prone to peeling between the solid electrolyte and the negative electrode active material layer or positive electrode active material layer due to the expansion and contraction of the negative electrode and positive electrode that occur during charging and discharging, which leads to deterioration of the battery.

[0004] As a method for suppressing peeling between the solid electrolyte and the negative electrode active material layer or the positive electrode active material layer, a technique of constraining an all-solid-state battery in a high-pressure pressed state is known. For example, Patent Document 1 discloses a method for manufacturing a battery, including a lamination step of preparing a laminate having a positive electrode current collector, a positive electrode layer, an electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order, a pressurizing step of pressurizing the laminate prepared in the lamination step in the stacking direction, and a restraining step of restraining the laminate while pressing it in the stacking direction at a pressure of 0.1 MPa to 100 MPa for a predetermined time after the pressurizing step. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-142228 A Summary of the Invention [Problem to be solved by the invention]

[0006] In order to suppress peeling between the solid electrolyte and the negative electrode active material layer and the positive electrode active material layer in the usage environment of the all-solid-state battery, it is desirable to constrain the solid electrolyte and the negative electrode active material layer and the positive electrode active material layer by high pressure pressing from the outside of the exterior material of the all-solid-state battery.

[0007] On the other hand, in recent years, with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., all-solid-state batteries are required to have a variety of shapes, as well as to be thin and lightweight. However, metal exterior materials that have been widely used in batteries have the disadvantage that it is difficult to keep up with the diversification of shapes and there is also a limit to the weight reduction. Therefore, a film-like exterior material in which a substrate / metal foil layer / thermally adhesive resin layer are sequentially laminated has been proposed as an exterior material that can be easily processed into a variety of shapes and can achieve a thin and lightweight structure.

[0008] In such a film-like exterior material, a space for accommodating a battery element is generally provided by forming the material into a bag shape or by forming the material using a mold, and battery elements such as electrodes and a solid electrolyte are disposed in the space, and the heat-fusible resin layers are heat-fused together to obtain an all-solid-state battery in which the battery element is accommodated inside the exterior material.

[0009] By applying such film-like exterior materials to the exterior materials of all-solid-state batteries, it is expected that the weight of electric vehicles, hybrid electric vehicles, etc. can be reduced.

[0010] As described above, in order to suppress peeling between the solid electrolyte and the negative electrode active material layer or the positive electrode active material layer even during use, it is desirable to restrain the all-solid-state battery by a high-pressure press from the outside of the exterior material.

[0011] However, after investigations, the inventors of the present disclosure found that when high-pressure pressing is performed from the outside of a film-like exterior material, it is extremely difficult to apply high-pressure pressing so that uniform pressure is applied to the entire surface of the pressed surface of the exterior material, and in particular, higher pressure is applied to the peripheral portion of the pressed surface of the exterior material than to the central portion, resulting in uneven restraint by the high-pressure press.

[0012] Under such circumstances, a main object of the present disclosure is to provide an exterior material for an all-solid-state battery that enables uniform pressing on the press surface of the all-solid-state battery. [Means for solving the problem]

[0013] The inventors of the present disclosure conducted intensive research to solve the above problems, and as a result, found that in an exterior packaging material for an all-solid-state battery, which is composed of a laminate including at least a base layer, a barrier layer, and a heat-sealable resin layer in this order from the outside, by providing a layer having a buffer function on the outside of the heat-sealable resin layer of the laminate constituting the exterior packaging material, the layer having the buffer function functions as a pressure buffer layer against high pressure pressing, and enables uniform pressing on the press surface of the all-solid-state battery.

[0014] The present disclosure has been completed based on these findings and through further investigations. That is, the present disclosure provides the invention of the following aspects. An exterior material for an all-solid-state battery, comprising a laminate including at least a base layer, a barrier layer, and a heat-sealable resin layer in this order from the outside, The laminate has a layer having a buffer function on an outer side of the thermally adhesive resin layer. Effect of the Invention

[0015] According to the present disclosure, it is possible to provide an exterior material for an all-solid-state battery that enables uniform pressing on the press surface of the all-solid-state battery. In addition, according to the present disclosure, it is also possible to provide a method for producing an exterior material for an all-solid-state battery, and an all-solid-state battery. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic diagram showing an example of a cross-sectional structure of an all-solid-state battery to which an exterior material for an all-solid-state battery according to the present disclosure is applied. [Diagram 2] FIG. 1 is a schematic diagram showing an example of a cross-sectional structure of an all-solid-state battery to which an exterior material for an all-solid-state battery according to the present disclosure is applied. [Diagram 3] FIG. 1 is a schematic plan view of an example of an all-solid-state battery to which an exterior material for an all-solid-state battery according to the present disclosure is applied. [Figure 4] FIG. 2 is a schematic cross-sectional view showing an example of a laminate structure of an exterior material for an all-solid-state battery according to the present disclosure. [Diagram 5] FIG. 2 is a schematic cross-sectional view showing an example of a laminate structure of an exterior material for an all-solid-state battery according to the present disclosure. [Figure 6] FIG. 2 is a schematic cross-sectional view showing an example of a laminate structure of an exterior material for an all-solid-state battery according to the present disclosure. [Figure 7] FIG. 2 is a schematic cross-sectional view showing an example of a laminate structure of an exterior material for an all-solid-state battery according to the present disclosure. [Figure 8] FIG. 2 is a schematic cross-sectional view showing an example of a laminate structure of an exterior material for an all-solid-state battery according to the present disclosure. [Figure 9] FIG. 2 is a schematic cross-sectional view showing an example of a laminate structure of an exterior material for an all-solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The all-solid-state battery packaging material of the present disclosure is a packaging material for all-solid-state batteries that is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order from the outside, and is characterized in that the laminate constituting the packaging material has a layer having a buffer function outside the heat-sealable resin layer. The all-solid-state battery packaging material of the present disclosure has this configuration, which enables uniform pressing of the press surface of the all-solid-state battery. More specifically, even when the all-solid-state battery is restrained by a high-pressure press, uniform pressing (i.e., the pressure applied to the press surface of the all-solid-state battery is uniform) can be performed on the press surface of the all-solid-state battery.

[0018] The exterior material for an all-solid-state battery according to the present disclosure will be described in detail below. In this specification, the numerical range indicated by "to" means "not less than" or "not more than." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.

[0019] 1.Layer structure of exterior materials for solid-state batteries The all-solid-state battery packaging material 10 of the present disclosure is composed of a laminate including at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 in this order from the outside, as shown in, for example, FIG. 4 to FIG. 9. Furthermore, the laminate constituting the all-solid-state battery packaging material 10 of the present disclosure has a layer having a buffer function (hereinafter, may be referred to as a "buffer layer 6") on the outside of the heat-sealable resin layer 4. In the all-solid-state battery packaging material 10, the heat-sealable resin layer 4 is the innermost layer. When assembling an all-solid-state battery using the all-solid-state battery packaging material 10 and a battery element, the battery element is accommodated in a space formed by heat-sealing the peripheral parts while the heat-sealable resin layers 4 of the all-solid-state battery packaging material 10 are opposed to each other. As described later, the base material layer 1 located on the outermost layer side may be made to constitute the buffer layer 6, which is a layer having a buffer function, by imparting a cushioning function (a function of dispersing pressure) to the base material layer 1 (see FIG. 7).

[0020] The all-solid-state battery exterior material 10 may have an adhesive layer 2 between the base material layer 1 and the barrier layer 3, as necessary, for the purpose of increasing the adhesion between these layers, as shown in Figs. 5, 6, 8, and 9, for example. In addition, an adhesive layer 5 may be provided between the barrier layer 3 and the heat-sealable resin layer 4, as necessary, for the purpose of increasing the adhesion between these layers, as shown in Fig. 6, for example. In addition, although not shown, a surface coating layer or the like may be provided on the outer side of the base material layer 1 (the side opposite to the heat-sealable resin layer 4 side) as necessary.

[0021] In the laminate constituting the all-solid-state battery packaging material 10, the buffer layer 6 is provided outside the heat-sealable resin layer 4, preferably outside the barrier layer 3. As shown in the schematic diagrams of FIGS. 4 to 6, the buffer layer 6 can be provided, for example, outside the base layer 1, specifically, on the side of the base layer 1 opposite to the barrier layer 3. Also, as shown in the schematic diagram of FIG. 7, the base layer 1 may constitute the buffer layer 6. The buffer layer 6 and the base layer 1 can be bonded together by an adhesive layer 2 or the like. Also, as shown in the schematic diagram of FIG. 8, the buffer layer 6 can be provided between the base layer 1 and the barrier layer 3. When the buffer layer 6 is provided between the base layer 1 and the barrier layer 3, for example, as shown in the schematic diagram of FIG. 8, the buffer layer 6 can be bonded to the base layer 1 and the barrier layer 3 by an adhesive layer 2 or the like. Also, as shown in the schematic diagram of FIG. 9, the buffer layer 6 can be provided between the barrier layer 3 and the heat-sealable resin layer 4.

[0022] The buffer layer 6 provided in the laminate may be one layer or two or more layers. When two or more buffer layers 6 are provided, the multiple buffer layers 6 may be provided adjacent to each other, or may be provided with a base layer 1, a barrier layer 3, or the like interposed therebetween.

[0023] Specific examples of the laminated structure of the all-solid-state battery exterior material 10 include the following laminated structures: A laminated structure in which a buffer layer 6 / a substrate layer 1 / a barrier layer 3 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a buffer layer 6, a base material layer 1, an adhesive layer 2, a barrier layer 3, and a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a buffer layer 6, a base layer 1, an adhesive layer 2, a barrier layer 3, an adhesive layer 5, and a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1 having a buffer function (which also functions as a buffer layer 6), a barrier layer 3, and a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1 having a buffer function (which also functions as a buffer layer 6), an adhesive layer 2, a barrier layer 3, and a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1 having a buffer function (which also functions as a buffer layer 6) / an adhesive layer 2 / a barrier layer 3 / an adhesive layer 5 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a buffer layer 6, an adhesive layer 2, a substrate layer 1, a barrier layer 3, and a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a buffer layer 6 / an adhesive layer 2 / a base layer 1 / an adhesive layer 2 / a barrier layer 3 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a buffer layer 6 / an adhesive layer 2 / a base layer 1 / an adhesive layer 2 / a barrier layer 3 / an adhesive layer 5 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1 / an adhesive layer 2 / a buffer layer 6 / an adhesive layer 2 / a barrier layer 3 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1 / an adhesive layer 2 / a buffer layer 6 / an adhesive layer 2 / a barrier layer 3 / an adhesive layer 5 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a buffer layer 6 / a base layer 1 / an adhesive layer 2 / a buffer layer 6 / an adhesive layer 2 / a barrier layer 3 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a buffer layer 6 / a base layer 1 / an adhesive layer 2 / a buffer layer 6 / an adhesive layer 2 / a barrier layer 3 / an adhesive layer 5 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1, a barrier layer 3, a buffer layer 6, and a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1, an adhesive layer 2, a barrier layer 3, a buffer layer 6, and a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1 / an adhesive layer 2 / a barrier layer 3 / an adhesive layer 5 / a buffer layer 6 / a heat-sealable resin layer 4 are laminated in this order; A laminated structure in which a base layer 1 / adhesive layer 2 / barrier layer 3 / buffer layer 6 / adhesive layer 5 / thermally adhesive resin layer 4 are laminated in this order.

[0024] The thickness of the laminate constituting the all-solid-state battery exterior material 10 is not particularly limited, but from the viewpoint of cost reduction, energy density improvement, and the like, it is preferably about 10,000 μm or less, about 8,000 μm or less, or about 5,000 μm or less, and from the viewpoint of maintaining the function of the all-solid-state battery exterior material to protect the battery element, it is preferably about 100 μm or more, about 150 μm or more, or about 200 μm or more, and preferred ranges include, for example, about 100 to 10,000 μm, about 100 to 8,000 μm, about 100 to 5,000 μm, about 150 to 10,000 μm, about 150 to 8,000 μm, about 150 to 5,000 μm, about 200 to 10,000 μm, about 200 to 8,000 μm, or about 200 to 5,000 μm. When the all-solid-state battery exterior material 10 is applied to an all-solid-state battery, the thickness of the buffer layer is reduced by high-pressure pressing, and the thickness of the laminate may also be reduced.

[0025] The details of each layer constituting the exterior material 10 for an all-solid-state battery will be described in detail in the section "3. Each layer constituting the exterior material for an all-solid-state battery."

[0026] 2.All-solid-state battery The all-solid-state battery to which the all-solid-state battery exterior material 10 of the present disclosure (hereinafter sometimes referred to as "exterior material 10") is applied is not particularly limited, except for the use of a specific exterior material 10. In other words, the battery elements (electrodes, solid electrolyte, terminals, etc.) other than the exterior material 10 are not particularly limited as long as they are applicable to all-solid-state batteries, and may be those used in known all-solid-state batteries. Hereinafter, an embodiment in which the all-solid-state battery exterior material 10 of the present disclosure is applied to an all-solid-state battery will be specifically described, taking the all-solid-state battery 70 of the present disclosure as an example.

[0027] As shown in the schematic diagrams of FIG. 1 to FIG. 3, the all-solid-state battery 70 of the present disclosure is a battery element including at least a single cell 50 including a positive electrode active material layer 31, a negative electrode active material layer 21, and a solid electrolyte layer 40 laminated between the positive electrode active material layer 31 and the negative electrode active material layer 21, which is housed in a package formed by the all-solid-state battery exterior material 10 of the present disclosure. More specifically, the positive electrode active material layer 31 is laminated on the positive electrode current collector 32 to form the positive electrode layer 30, and the negative electrode active material layer 21 is laminated on the negative electrode current collector 22 to form the negative electrode layer 20. The positive electrode current collector 32 and the negative electrode current collector 22 are each joined to a terminal 60 exposed to the outside and electrically connected to the external environment. The solid electrolyte layer 40 is laminated between the positive electrode layer 30 and the negative electrode layer 20, and the positive electrode layer 30, the negative electrode layer 20, and the solid electrolyte layer 40 form the single cell 50. The battery element of the all-solid-state battery 70 may include only one unit cell 50, or may include a plurality of unit cells 50. Fig. 1 illustrates an all-solid-state battery 70 including one unit cell 50 as a battery element, and Fig. 2 illustrates an all-solid-state battery 70 in which two unit cells 50 are stacked to form a battery element.

[0028] In the all-solid-state battery 70, the battery element is covered in a manner that allows a flange portion (a region where the heat-sealable resin layers contact each other) to be formed on the periphery of the battery element with the terminals 60 connected to the positive electrode layer 30 and the negative electrode layer 20 protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to form a hermetic seal, thereby forming an all-solid-state battery using an exterior material for an all-solid-state battery. When a battery element is housed in a package formed from the exterior material for an all-solid-state battery of the present disclosure, the package is formed so that the heat-sealable resin portion of the exterior material for an all-solid-state battery of the present disclosure faces inside (the surface in contact with the battery element).

[0029] As shown in the schematic diagram of FIG. 3, in the all-solid-state battery 70 of the present disclosure, when high-pressure pressing is performed from the outside of the exterior material 10, high-pressure pressing is performed on the entire press surface 11 of the exterior material 10 (for example, the area surrounded by the two-dot chain line in the schematic diagram of FIG. 3).

[0030] Specifically, as described above, in the past, in order to suppress peeling between the solid electrolyte and the negative electrode active material layer and the positive electrode active material layer, it is desirable to restrain the all-solid-state battery under high pressure from the outside of the exterior material. When the all-solid-state battery 70 is viewed in plan, high pressure is applied to the battery element portion of the all-solid-state battery when the all-solid-state battery 70 is restrained under high pressure. The inventors of the present disclosure have found that when a film-like exterior material is pressed from the outside, it is extremely difficult to press the exterior material with high pressure so that a uniform pressure is applied to the entire surface of the pressed surface of the exterior material, and in particular, a higher pressure is applied to the outer periphery of the pressed surface of the exterior material than to the center portion, and the restraint by the high pressure press is non-uniform. In the exterior material 10 for all-solid-state batteries of the present disclosure, the laminate constituting the exterior material 10 has a buffer layer on the outside (barrier layer 3 side) of the heat-sealable resin layer 4. Therefore, on the press surface 11 to which high pressure is applied to the all-solid-state battery, the buffer layer 6 functions as a cushion to distribute the pressure applied to the press surface 11 of the exterior material 10, enabling uniform pressing of the press surface of the all-solid-state battery. By applying uniform pressing to the press surface of the all-solid-state battery, for example, peeling between the solid electrolyte and the positive electrode active material layer can be more suitably suppressed.

[0031] In general, in an all-solid-state battery, when the all-solid-state battery is viewed in plan, the area of ​​the positive electrode active material layer 31 is equal to or smaller than the area of ​​the negative electrode active material layer 21. In addition, the portion of the all-solid-state battery that is pressed under high pressure generally corresponds to the portion where the positive electrode active material layer is present. As shown in the schematic diagram of FIG. 3, it is preferable that the pressing surface 11 of the exterior material 10 is equal to or smaller than the area of ​​the positive electrode active material layer 31.

[0032] As described above, the all-solid-state battery to which the exterior material 10 of the present disclosure is applied is not particularly limited, with the limitation that a specific exterior material 10 is used, and the same is true for the all-solid-state battery 70 of the present disclosure. Hereinafter, examples of materials constituting the battery element of the all-solid-state battery to which the exterior material 10 of the present disclosure is applied will be described. As shown in the schematic diagrams of FIGS. 1 and 2, when the battery element is sealed by opposing two exterior materials to form the all-solid-state battery 70, the all-solid-state battery 70 of the present disclosure may have at least one exterior material made of the exterior material 10 of the present disclosure, but from the viewpoint of enabling uniform pressing of the press surface of the all-solid-state battery, it is preferable that the exterior materials on both sides are made of the exterior material 10 of the present disclosure. When the all-solid-state battery is laminated to form a module, the exterior material 10 of the present disclosure may be applied to the exterior material on one side.

[0033] As described above, the battery element of the all-solid-state battery 70 includes at least the positive electrode layer 30, the negative electrode layer 20, and the solid electrolyte layer 40 constituting a single cell 50. The positive electrode layer 30 has a structure in which a positive electrode active material layer 31 is laminated on a positive electrode current collector 32. The negative electrode layer 20 has a structure in which a negative electrode active material layer 21 is laminated on a negative electrode current collector 22. The positive electrode current collector 32 and the negative electrode current collector 22 are each joined to a terminal 60 exposed to the outside, and are electrically connected to the external environment.

[0034] [Cathode active material layer 31] The positive electrode active material layer 31 is a layer containing at least a positive electrode active material. In addition to the positive electrode active material, the positive electrode active material layer 31 may further contain a solid electrolyte material, a conductive material, a binder, and the like, as necessary.

[0035] The positive electrode active material is not particularly limited, and examples thereof include oxide active materials, sulfide active materials, etc. When the all-solid-state battery is an all-solid-state lithium battery, examples of the oxide active material used as the positive electrode active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn1.5 Examples of the sulfide active material used as the positive electrode active material of the all-solid-state lithium battery include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li2FeSiO4 and Li2MnSiO4. Examples of the sulfide active material used as the positive electrode active material of the all-solid-state lithium battery include copper chevrel, iron sulfide, cobalt sulfide, and nickel sulfide.

[0036] The shape of the positive electrode active material is not particularly limited, but may be, for example, a particulate shape. 50 ) is preferably, for example, about 0.1 to 50 μm. The content of the positive electrode active material in the positive electrode active material layer 31 is preferably about 10 to 99 mass %, and more preferably about 20 to 90 mass %.

[0037] The positive electrode active material layer 31 preferably further contains a solid electrolyte material. This can improve the ion conductivity in the positive electrode active material layer 31. The solid electrolyte material contained in the positive electrode active material layer 31 is the same as the solid electrolyte material exemplified for the solid electrolyte layer 40 described later. The content of the solid electrolyte material in the positive electrode active material layer is preferably about 1 to 90 mass %, more preferably about 10 to 80 mass %.

[0038] The positive electrode active material layer 31 may further contain a conductive material. The addition of a conductive material can improve the electronic conductivity of the positive electrode active material layer. Examples of the conductive material include acetylene black, ketjen black, and carbon fiber. The positive electrode active material layer may further contain a binder. Examples of the binder include fluorine-containing binders such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).

[0039] The thickness of the positive electrode active material layer 31 is appropriately set depending on the size of the all-solid-state battery and the like, but is preferably about 0.1 to 1000 μm.

[0040] [Positive electrode current collector 32] Examples of materials that can be used to form the positive electrode current collector 32 include stainless steel (SUS), aluminum, nickel, iron, titanium, and carbon.

[0041] The thickness of the positive electrode current collector 32 is appropriately set depending on the size of the all-solid-state battery and the like, but is preferably about 10 to 1000 μm.

[0042] [Negative electrode active material layer 21] The negative electrode active material layer 21 is a layer containing at least a negative electrode active material. In addition to the negative electrode active material, the negative electrode active material layer 21 may contain a solid electrolyte material, a conductive material, a binder, and the like, as necessary.

[0043] The negative electrode active material is not particularly limited, and examples thereof include carbon active materials, metal active materials, and oxide active materials. Examples of carbon active materials include mesocarbon microbeads (MCMB), graphite such as highly oriented graphite (HOPG), and amorphous carbon such as hard carbon and soft carbon. Examples of metal active materials include In, Al, Si, and Sn. Examples of oxide active materials include Nb2O5, Li4Ti5O 12 , SiO, etc.

[0044] The shape of the negative electrode active material is not particularly limited, but examples thereof include a particle shape and a film shape. 50 ) is preferably about 0.1 to 50 μm. The content of the negative electrode active material in the negative electrode active material layer 21 is, for example, about 10 to 99 mass %, and more preferably about 20 to 90 mass %.

[0045] The negative electrode active material layer 21 preferably further contains a solid electrolyte material. This can improve the ion conductivity in the negative electrode active material layer 21. The solid electrolyte material contained in the negative electrode active material layer 21 is the same as the solid electrolyte material exemplified in the solid electrolyte layer 40 described later. The content of the solid electrolyte material in the negative electrode active material layer 21 is preferably about 1 to 90 mass %, more preferably about 10 to 80 mass %.

[0046] The negative electrode active material layer 21 may further contain a conductive material. The negative electrode active material layer 21 may further contain a binder. The conductive material and the binder are the same as those exemplified for the positive electrode active material layer 31 described above.

[0047] The thickness of the negative electrode active material layer 21 is appropriately set depending on the size of the all-solid-state battery and the like, but is preferably about 0.1 to 1000 μm.

[0048] [Negative electrode current collector 22] Examples of materials that can be used to form the negative electrode current collector 22 include stainless steel (SUS), copper, nickel, and carbon.

[0049] The thickness of the negative electrode current collector 22 is appropriately set depending on the size of the all-solid-state battery and the like, but is preferably about 10 to 1000 μm.

[0050] [Solid electrolyte layer 40] The solid electrolyte layer 40 is a layer containing a solid electrolyte material. Examples of the solid electrolyte material include a sulfide solid electrolyte material and an oxide solid electrolyte material.

[0051] Sulfide solid electrolyte materials are preferred in that many of them have higher ion conductivity than oxide solid electrolyte materials, and oxide solid electrolyte materials are preferred in that they have higher chemical stability than sulfide solid electrolyte materials.

[0052] Specific examples of oxide solid electrolyte materials include compounds having a NASICON structure. One example of a compound having a NASICON structure is represented by the general formula Li 1+x Al x Ge 2-x (PO4)3 (0≦x≦2) is one of the compounds represented by the formula: 1.5 Al 0.5 Ge 1.5(PO4)3 is preferred. Another example of a compound having a NASICON structure is a compound having the general formula Li 1+x AlxTi 2-x (PO4)3 (0≦x≦2) is an example of a compound represented by the formula: 1.5 Al 0.5 Ti 1.5 (PO4)3 is preferable. Another example of the oxide solid electrolyte material used in the all-solid-state lithium secondary battery is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.

[0053] Specific examples of sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2SP2S5-ZmSn (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers; M is any of P, Si, Ge, B, Al, Ga, and In). The above description of "Li2S-P2S5" means a sulfide solid electrolyte material made using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. The sulfide solid electrolyte material may be a sulfide glass or a crystallized sulfide glass.

[0054] The content of the solid electrolyte material in the solid electrolyte layer 40 is not particularly limited, but is preferably 60 mass % or more, more preferably 70 mass % or more, and further preferably 80 mass % or more. The solid electrolyte layer may contain a binder, or may be composed of only the solid electrolyte material.

[0055] The thickness of the solid electrolyte layer 40 is appropriately set depending on the size of the all-solid-state battery and the like, but is preferably about 0.1 to 1000 μm, and more preferably about 0.1 to 300 μm.

[0056] The all-solid-state battery 70 of the present disclosure can be suitably used in an environment where it is constrained from the outside under high pressure. The pressure for constraining the all-solid-state battery 70 from the outside is preferably about 0.1 MPa or more, more preferably 5 MPa or more, and even more preferably about 1 MPa or more, from the viewpoint of suitably suppressing peeling between the solid electrolyte and the negative electrode active material layer or the positive electrode active material layer, and is preferably about 100 MPa or less, more preferably about 30 MPa or less, and preferred ranges include about 0.1 to 100 MPa, about 0.1 to 70 MPa, about 5 to 100 MPa, about 5 to 70 MPa, about 10 to 100 MPa, and about 1 to 30 MPa. Examples of a method for constraining the all-solid-state battery 70 from the outside under high pressure include a method in which the all-solid-state battery is sandwiched between metal plates and fixed in a high-pressure pressed state (for example, clamped with a vice).

[0057] From the same viewpoint, the temperature when restraining the all-solid-state battery 70 from the outside is preferably 20° C. or higher, more preferably 40° C. or higher, and is preferably 200° C. or lower, more preferably 150° C. or lower, and preferred ranges include about 20 to 150° C., about 40 to 150° C.

[0058] 3. Layers that form the exterior material for solid-state batteries The exterior packaging material 10 of the present disclosure is composed of a laminate having at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 in this order from the outside, and further, the laminate has a buffer layer 6 outside the heat-sealable resin layer 4. Each layer constituting the exterior packaging material 10 of the present disclosure will be described in detail below.

[0059] [Buffer layer 6] In the present disclosure, the buffer layer 6 is provided on the barrier layer 3 side of the heat-sealable resin layer 4 in order to enable uniform pressing on the pressing surface of the solid-state battery, and is a layer that exhibits a cushioning function against high-pressure pressing (has a pressure buffering function).

[0060] As shown in the schematic diagrams of FIGS. 4 to 6, the buffer layer 6 can be provided outside the heat-sealable resin layer 4, preferably outside the barrier layer 3, and further outside the base layer 1. As shown in the schematic diagram of FIG. 7, the base layer 1 can also constitute the buffer layer. The buffer layer 6 and the base layer 1 can be bonded together by an adhesive layer 2 or the like. Also, as shown in the schematic diagram of FIG. 8, the buffer layer 6 can be provided between the base layer 1 and the barrier layer 3. When the buffer layer 6 is provided between the base layer 1 and the barrier layer 3, for example, as shown in the schematic diagram of FIG. 8, the buffer layer 6 can be bonded to the base layer 1 and the barrier layer 3 by using an adhesive layer 2 or the like. Also, as shown in the schematic diagram of FIG. 9, the buffer layer 6 can be provided between the barrier layer 3 and the heat-sealable resin layer 4.

[0061] The buffer layer 6 provided in the laminate may be one layer or two or more layers. When two or more buffer layers 6 are provided, the multiple buffer layers 6 may be provided adjacent to each other, or may be provided with a base layer 1, a barrier layer 3, or the like interposed therebetween.

[0062] As described above, in general, in an all-solid-state battery, when the all-solid-state battery is viewed from above, the area of ​​the positive electrode active material layer 31 is equal to or smaller than the area of ​​the negative electrode active material layer 21. In addition, the portion of the all-solid-state battery that is pressed under high pressure generally corresponds to the portion where the positive electrode active material layer is present. As shown in the schematic diagram of FIG. 3, it is preferable that the pressing surface 11 of the exterior material 10 is equal to or smaller than the area of ​​the positive electrode active material layer 31.

[0063] The material constituting the buffer layer 6 is not particularly limited as long as it can function as a cushion against a high pressure press (capable of dispersing pressure), and preferred examples include rubber, nonwoven fabric, and foam sheet.

[0064] The rubber is not particularly limited as long as it has elasticity, and examples thereof include natural rubber, fluororubber, silicone rubber, etc. The rubber hardness is preferably about 20 to 90.

[0065] The material constituting the nonwoven fabric is not particularly limited, and preferably includes the same resin as exemplified in the below-described base layer 1. Since the all-solid-state battery is expected to be used in a high-temperature environment, it is preferable that the nonwoven fabric is made of a material having excellent heat resistance.

[0066] In order to uniformly distribute the pressure applied by the high-pressure press, the weight of the nonwoven fabric is preferably about 20 g / m 2 More preferably, about 30 g / m 2 More preferably, 100 g / m 2 or more, and preferably about 300 g / m 2 Less than or equal to about 200 g / m 2 The following are included, and the preferred range is 20 to 300 g / m 2 degree, 20~200g / m 2 degree, 30~300g / m 2 degree, 30~200g / m 2 degree, 100~300g / m 2 degree, 100~200g / m 2 Among these, 100 to 300 g / m2 degree, 100~200g / m 2 degree is particularly preferred.

[0067] From the viewpoint of uniformly distributing the pressure from the high-pressure press, the fiber diameter of the fibers constituting the nonwoven fabric is preferably about 5 μm or more, more preferably about 15 μm or more, and is preferably 60 μm or less, more preferably about 40 μm or less. Preferred ranges include about 5 to 60 μm, about 5 to 40 μm, about 15 to 60 μm, and about 15 to 40 μm, and is particularly preferably about 5 to 40 μm.

[0068] The thickness of the buffer layer 6 is not particularly limited as long as it can uniformly disperse the pressure of the high pressure press, and is preferably about 55 μm or more, more preferably about 75 μm or more, and is preferably about 10,000 μm or less, more preferably about 8,000 μm or less, with a preferred range of about 55 to 8,000 μm. In particular, when the buffer layer 6 is made of a nonwoven fabric, the thickness of the buffer layer 6 is preferably about 100 μm or more, about 200 μm or more, about 1,000 μm or more, and is also preferably about 5,000 μm or less, and about 3,000 μm or less, with preferred ranges of about 100 to 5,000 μm, about 100 to 3,000 μm, about 200 to 5,000 μm, about 200 to 3,000 μm, about 1,000 to 5,000 μm, and about 1,000 to 3,000 μm, with 1,000 to 3,000 μm being particularly preferred. In particular, when the buffer layer 6 is made of rubber, the thickness of the buffer layer 6 is preferably about 10 mm or less, about 5 mm or less, about 2 mm or less, or about 0.5 mm or more, and preferred ranges include about 0.5 to 10 mm, about 0.5 to 5 mm, and about 0.5 to 2 mm.

[0069] [Base material layer 1] In the present disclosure, the substrate layer 1 is a layer provided for the purpose of exhibiting the function as a substrate of the exterior material for an all-solid-state battery, etc. The substrate layer 1 is located on the outer layer side of the exterior material for an all-solid-state battery.

[0070] The material forming the base layer 1 is not particularly limited as long as it has the function of a base, that is, at least insulating properties. The base layer 1 can be formed using, for example, a resin, and the resin may contain additives described later.

[0071] In addition, when the base layer 1 can exhibit a pressure buffering function of uniformly dispersing the pressure from a high-pressure press, the base layer 1 may constitute a buffer layer 6, which is a layer having a buffering function. Specifically, when the base layer 1 is made of the rubber or nonwoven fabric exemplified in the above item [Buffer layer 6], the base layer 1 can constitute the buffer layer 6, and it is not necessary to provide a separate buffer layer 6 in addition to the base layer 1 functioning as the buffer layer 6.

[0072] When the base layer 1 is made of a resin, the base layer 1 may be, for example, a resin film formed of a resin, or may be formed by applying a resin. Generally, resin films and those formed by applying a resin are generally hard, and it is difficult to uniformly disperse the pressure of a high-pressure press. For this reason, when the base layer 1 is made of these, it is difficult for the base layer 1 to constitute the buffer layer 6, and it is preferable to provide the buffer layer 6 separately from the base layer 1.

[0073] When the base layer 1 is made of a resin film, the resin film may be an unstretched film or a stretched film. Examples of stretched films include uniaxially stretched films and biaxially stretched films, and biaxially stretched films are preferred. Examples of stretching methods for forming biaxially stretched films include sequential biaxial stretching, inflation, and simultaneous biaxial stretching. Examples of methods for applying a resin include roll coating, gravure coating, and extrusion coating.

[0074] Examples of the resin forming the base layer 1 include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, and phenol resin, as well as modified versions of these resins. The resin forming the base layer 1 may be a copolymer of these resins or a modified version of the copolymer. Furthermore, it may be a mixture of these resins.

[0075] Of these, preferred examples of the resin forming the base layer 1 include polyester and polyamide.

[0076] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters. Examples of copolymerized polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit. Specific examples of polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit and is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), and polyethylene (terephthalate / decane dicarboxylate). These polyesters may be used alone or in combination of two or more.

[0077] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) that contain structural units derived from terephthalic acid and / or isophthalic acid, and polyamides containing aromatic compounds such as polyamide MXD6 (polymetaxylylene adipamide); alicyclic polyamides such as polyamide PACM6 (polybis(4-aminocyclohexyl)methane adipamide); polyamides copolymerized with a lactam component or an isocyanate component such as 4,4'-diphenylmethane diisocyanate; polyesteramide copolymers and polyetheresteramide copolymers that are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and polyamides such as copolymers of these copolymers. These polyamides may be used alone or in combination of two or more.

[0078] The base layer 1 preferably includes at least one of a polyester film, a polyamide film, and a polyolefin film, preferably includes at least one of a stretched polyester film, a stretched polyamide film, and a stretched polyolefin film, more preferably includes at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film, and a stretched polypropylene film, and even more preferably includes at least one of a biaxially oriented polyethylene terephthalate film, a biaxially oriented polybutylene terephthalate film, a biaxially oriented nylon film, and a biaxially oriented polypropylene film.

[0079] The base layer 1 may be a single layer, or may be composed of two or more layers. When the base layer 1 is composed of two or more layers, the base layer 1 may be a laminate in which resin films are laminated with an adhesive or the like, or may be a laminate of resin films formed by co-extrusion of resins into two or more layers. In addition, a laminate of resin films formed by co-extrusion of resins into two or more layers may be used as the base layer 1 without being stretched, or may be uniaxially or biaxially stretched to form the base layer 1. When the base layer 1 is a single layer, the base layer 1 is preferably composed of a single layer of polyester resin.

[0080] In the base layer 1, specific examples of the laminate of two or more resin films include a laminate of a polyester film and a nylon film, a laminate of two or more nylon films, and a laminate of two or more polyester films, and preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more stretched nylon films, and a laminate of two or more stretched polyester films. For example, when the base layer 1 is a laminate of two resin films, a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film is preferred, and a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film is more preferred.

[0081] When the base layer 1 is a laminate of two or more resin films, the two or more resin films may be laminated via an adhesive. Preferred adhesives include the same adhesives as those exemplified in the adhesive layer 2 described later. The method for laminating two or more resin films is not particularly limited, and known methods can be adopted, such as dry lamination, sandwich lamination, extrusion lamination, and thermal lamination, and preferably dry lamination. When laminating by the dry lamination method, it is preferable to use a polyurethane adhesive as the adhesive. In this case, the thickness of the adhesive is, for example, about 2 to 5 μm. Also, an anchor coat layer may be formed on the resin film and laminated. The anchor coat layer may be the same adhesive as that exemplified in the adhesive layer 2 described later. In this case, the thickness of the anchor coat layer is, for example, about 0.01 to 1.0 μm.

[0082] Furthermore, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the interior of the base layer 1. The additives may be used alone or in combination of two or more.

[0083] In the present disclosure, from the viewpoint of improving the moldability of the all-solid-state battery exterior material, it is preferable that a lubricant is present on the surface of the base material layer 1. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.

[0084] When a lubricant is present on the surface of the base layer 1, the amount of the lubricant is not particularly limited, but is preferably about 3 mg / m 2 More preferably, 4 to 15 mg / m 2 about 5 to 14 mg / m 2 The degree of

[0085] The lubricant present on the surface of the base layer 1 may be a lubricant exuded from the resin constituting the base layer 1, or a lubricant applied to the surface of the base layer 1.

[0086] The thickness of the substrate layer 1 is not particularly limited as long as it functions as a substrate, and may be, for example, about 3 to 50 μm, and preferably about 10 to 35 μm. When the substrate layer 1 is a laminate of two or more resin films, the thickness of each resin film constituting each layer is preferably about 2 to 25 μm. When the substrate layer 1 is a layer having a buffer function, the thickness of the substrate layer 1 is the thickness described in the above-mentioned [Buffer layer 6].

[0087] [Adhesive layer 2] In the exterior packaging material for an all-solid-state battery of the present disclosure, the adhesive layer 2 is a layer that is provided between the base layer 1 and the barrier layer 3 as necessary for the purpose of increasing the adhesion between them.

[0088] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 is not limited, and may be any of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressure type, etc. Also, it may be a two-component curing adhesive (two-component adhesive), a one-component curing adhesive (one-component adhesive), or a resin that does not involve a curing reaction. Also, the adhesive layer 2 may be a single layer or multiple layers.

[0089] Specific examples of adhesive components contained in the adhesive include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymerized polyamides; polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred. In addition, the adhesive strength of these adhesive component resins can be increased by using an appropriate curing agent in combination. The curing agent is selected from polyisocyanates, multifunctional epoxy resins, oxazoline group-containing polymers, polyamine resins, acid anhydrides, and the like, depending on the functional groups of the adhesive components.

[0090] The polyurethane adhesive may be, for example, a polyurethane adhesive containing a base agent containing a polyol compound and a curing agent containing an isocyanate compound.Preferably, a two-component curing type polyurethane adhesive may be used, in which a polyol such as polyester polyol, polyether polyol, or acrylic polyol is used as the base agent, and an aromatic or aliphatic polyisocyanate is used as the curing agent.In addition, as the polyol compound, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the hydroxyl group at the end of the repeating unit.

[0091] In addition, the adhesive layer 2 is allowed to contain other components as long as they do not impair adhesion, and may contain a colorant, a thermoplastic elastomer, a tackifier, a filler, etc. By containing a colorant in the adhesive layer 2, the exterior material for an all-solid-state battery can be colored. As the colorant, known colorants such as pigments and dyes can be used. In addition, only one type of colorant may be used, or two or more types may be mixed and used.

[0092] The type of pigment is not particularly limited as long as it does not impair the adhesiveness of the adhesive layer 2. Examples of organic pigments include azo-based, phthalocyanine-based, quinacridone-based, anthraquinone-based, dioxazine-based, indigothioindigo-based, perinone-perylene-based, isoindolenine-based, and benzimidazolone-based pigments, while examples of inorganic pigments include carbon black-based, titanium oxide-based, cadmium-based, lead-based, chromium oxide-based, and iron-based pigments, and other examples include fine powder of mica, fish scale foil, and the like.

[0093] Among colorants, carbon black is preferable in order to make the exterior material for an all-solid-state battery have a black appearance, for example.

[0094] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.

[0095] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the exterior material for an all-solid-state battery is colored, and may be, for example, about 5 to 60 mass %, and preferably 10 to 40 mass %.

[0096] The thickness of the adhesive layer 2 is not particularly limited as long as it can bond the base layer 1 and the barrier layer 3, and can be, for example, about 1 μm or more, about 2 μm or more, and about 10 μm or less, about 5 μm or less, and preferred ranges include about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, and about 2 to 5 μm.

[0097] [Colored layer] The colored layer is a layer (not shown) that is provided between the base material layer 1 and the barrier layer 3 as necessary. When the adhesive layer 2 is provided, a colored layer may be provided between the base material layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. Also, a colored layer may be provided on the outside of the base material layer 1. By providing a colored layer, the exterior material for an all-solid-state battery can be colored.

[0098] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1, the surface of the adhesive layer 2, or the surface of the barrier layer 3. As the colorant, known substances such as pigments and dyes can be used. Furthermore, only one type of colorant may be used, or two or more types may be mixed together.

[0099] Specific examples of the colorant contained in the colored layer include the same as those exemplified in the section [Adhesive layer 2].

[0100] [Barrier layer 3] In the exterior material for an all-solid-state battery, the barrier layer 3 is a layer that at least prevents the penetration of moisture.

[0101] Examples of the barrier layer 3 include metal foils, vapor-deposited films, and resin layers having barrier properties. Examples of the vapor-deposited films include metal vapor-deposited films, inorganic oxide vapor-deposited films, and carbon-containing inorganic oxide vapor-deposited films. Examples of the resin layer include fluorine-containing resins such as polyvinylidene chloride, polymers mainly composed of chlorotrifluoroethylene (CTFE), polymers mainly composed of tetrafluoroethylene (TFE), polymers having fluoroalkyl groups, and polymers mainly composed of fluoroalkyl units, and ethylene-vinyl alcohol copolymers. Examples of the barrier layer 3 include resin films having at least one of these vapor-deposited films and resin layers. The barrier layer 3 may be provided in a plurality of layers. The barrier layer 3 preferably includes a layer made of a metal material. Specific examples of the metal material constituting the barrier layer 3 include aluminum alloys, stainless steel, titanium steel, and steel plates. When used as a metal foil, it is preferable to include at least one of aluminum alloy foil and stainless steel foil.

[0102] From the viewpoint of improving the formability of the all-solid-state battery packaging material, the aluminum alloy foil is preferably a soft aluminum alloy foil made of, for example, an annealed aluminum alloy, and from the viewpoint of further improving the formability, the aluminum alloy foil is preferably an iron-containing aluminum alloy foil. In the iron-containing aluminum alloy foil (100 mass%), the iron content is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%. By having an iron content of 0.1 mass% or more, an all-solid-state battery packaging material having better formability can be obtained. By having an iron content of 9.0 mass% or less, an all-solid-state battery packaging material having better flexibility can be obtained. Examples of the soft aluminum alloy foil include aluminum alloy foils having a composition specified in JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, or JIS H4000:2014 A8079P-O. Silicon, magnesium, copper, manganese, etc. may be added as necessary. Softening can be performed by annealing or the like.

[0103] Examples of the stainless steel foil include austenitic, ferritic, austenitic-ferritic, martensitic, and precipitation hardened stainless steel foils. From the viewpoint of providing an exterior material for an all-solid-state battery having excellent formability, the stainless steel foil is preferably made of austenitic stainless steel.

[0104] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L, and among these, SUS304 is particularly preferred.

[0105] In the case of a metal foil, the thickness of the barrier layer 3 should be such that it at least functions as a barrier layer that prevents moisture from penetrating, and is, for example, about 9 to 200 μm. The thickness of the barrier layer 3 is, for example, preferably about 85 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, and particularly preferably about 35 μm or less, and is preferably about 10 μm or more, even more preferably about 20 μm or more, and more preferably about 25 μm or more, and preferred ranges of the thickness include about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm. When the barrier layer 3 is made of an aluminum alloy foil, the above-mentioned range is particularly preferred, with about 25 to 85 μm and about 25 to 50 μm being particularly preferred. In particular, when the barrier layer 3 is made of a stainless steel foil, the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, even more preferably about 30 μm or less, and particularly preferably about 25 μm or less, and is preferably about 10 μm or more, more preferably about 15 μm or more, and preferred thickness ranges include about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 25 μm, about 15 to 60 μm, about 15 to 50 μm, about 15 to 40 μm, about 15 to 30 μm, and about 15 to 25 μm.

[0106] In addition, when the barrier layer 3 is a metal foil, it is preferable to provide a corrosion-resistant film at least on the surface opposite to the base layer in order to prevent dissolution and corrosion due to corrosive gas generated from the solid electrolyte. The barrier layer 3 may be provided with a corrosion-resistant film on both sides. Here, the corrosion-resistant film refers to a thin film that is provided with corrosion resistance by performing, for example, hydrothermal conversion treatment such as boehmite treatment, chemical conversion treatment, anodizing treatment, plating treatment such as nickel or chromium, or corrosion prevention treatment by applying a coating agent on the surface of the barrier layer. As a treatment for forming a corrosion-resistant film, one type may be performed, or two or more types may be combined. In addition to one layer, multiple layers can be formed. Furthermore, among these treatments, hydrothermal conversion treatment and anodizing treatment are treatments in which the metal foil surface is dissolved by a treatment agent to form a metal compound having excellent corrosion resistance. Note that these treatments may be included in the definition of chemical conversion treatment. In addition, when the barrier layer 3 has a corrosion-resistant film, the corrosion-resistant film is also included in the barrier layer 3.

[0107] The corrosion-resistant coating prevents delamination between the barrier layer (e.g., aluminum alloy foil) and the substrate layer during molding of the exterior packaging material for the all-solid-state battery, prevents dissolution and corrosion of the barrier layer surface due to corrosive gas generated from the solid electrolyte, and in particular prevents dissolution and corrosion of aluminum oxide present on the barrier layer surface when the barrier layer is an aluminum alloy foil, and also improves the adhesion (wettability) of the barrier layer surface, thereby preventing delamination between the substrate layer and the barrier layer during heat sealing and between the substrate layer and the barrier layer during molding.

[0108] Various corrosion-resistant films formed by chemical conversion treatments are known, and mainly include corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds, and rare earth oxides. Examples of chemical conversion treatments using phosphates and chromates include chromate chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, and chromate treatment. Examples of chromium compounds used in these treatments include chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate. Examples of phosphorus compounds used in these treatments include sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid. Examples of chromate treatments include etching chromate treatment, electrolytic chromate treatment, and coating-type chromate treatment, and coating-type chromate treatment is preferred. In this coating type chromate treatment, at least the inner layer side of the barrier layer (e.g., aluminum alloy foil) is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is coated with a treatment liquid mainly composed of a metal phosphate such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, or Zn (zinc) phosphate, or a mixture of these metal salts, or a treatment liquid mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid consisting of a mixture of these with a synthetic resin, or the like, by a known coating method such as a roll coating method, a gravure printing method, or a dipping method, and then dried. As the treatment liquid, various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents can be used, and water is preferred. Examples of the resin component used here include polymers such as phenolic resins and acrylic resins, and chromate treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylic acid ester copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer, or a derivative thereof such as sodium salt, ammonium salt, or amine salt. In particular, a derivative of polyacrylic acid such as an ammonium salt, sodium salt, or amine salt of polyacrylic acid is preferable. In the present disclosure, polyacrylic acid means a polymer of acrylic acid. The acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride, and is also preferably an ammonium salt, sodium salt, or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride. Only one type of acrylic resin may be used, or two or more types may be mixed and used.

[0109] [ka]

[0110] [ka]

[0111] [ka]

[0112] [ka]

[0113] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the following formulae may be the same or different. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the general formulae (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000. The aminated phenol polymer can be prepared, for example, by polycondensing a phenol compound or a naphthol compound with formaldehyde to produce a polymer consisting of the repeating units represented by the above general formula (1) or (3), and then polycondensing the polymer with formaldehyde and an amine (R 1 R 2 NH) to the functional group (-CHNR 1 R 2 The aminated phenol polymers can be used alone or in combination of two or more.

[0114] Another example of the corrosion-resistant film is a thin film formed by a coating-type corrosion prevention treatment in which a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer is applied. The coating agent may further contain phosphoric acid or a phosphate, and a crosslinking agent for crosslinking the polymer. The rare earth element oxide sol has rare earth element oxide fine particles (for example, particles with an average particle size of 100 nm or less) dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide, and cerium oxide is preferred from the viewpoint of further improving adhesion. The rare earth element oxide contained in the corrosion-resistant film can be used alone or in combination of two or more. Examples of the liquid dispersion medium for the rare earth element oxide sol include various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents, and water is preferred. As the cationic polymer, for example, polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or its derivative, aminated phenol, etc. are preferable. In addition, as the anionic polymer, poly(meth)acrylic acid or its salt, or a copolymer mainly composed of (meth)acrylic acid or its salt, is preferable. In addition, it is preferable that the crosslinking agent is at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. In addition, it is preferable that the phosphoric acid or the phosphoric acid salt is a condensed phosphoric acid or a condensed phosphate salt.

[0115] One example of a corrosion-resistant coating is one formed by applying a solution of fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate dispersed in phosphoric acid to the surface of a barrier layer and baking the coating at 150°C or higher.

[0116] If necessary, the corrosion-resistant coating may have a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and anionic polymer include those mentioned above.

[0117] The composition of the corrosion-resistant film can be analyzed by, for example, time-of-flight secondary ion mass spectrometry.

[0118] The amount of the corrosion-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of coating-type chromate treatment, the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 is preferably 1 mm. 2 For example, the amount of the chromate compound is about 0.5 to 50 mg, preferably 1 It is desirable that the content of the phosphorus compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, in terms of phosphorus, and the aminated phenol polymer is, for example, about 1.0 to 200 mg, preferably about 5.0 to 150 mg.

[0119] The thickness of the corrosion-resistant film is not particularly limited, but is preferably about 1 nm to 20 μm, more preferably about 1 nm to 100 nm, and even more preferably about 1 nm to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the barrier layer and the heat-sealable resin layer. The thickness of the corrosion-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy. Analysis of the composition of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry can reveal that, for example, secondary ions consisting of Ce, P, and O (e.g., Ce2PO4 + , CePO4 - At least one of the following: CrPO2 + , CrPO4 - Peaks derived from at least one of the above are detected.

[0120] The chemical conversion treatment is carried out by applying a solution containing a compound used for forming a corrosion-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer becomes about 70 to 200°C. In addition, before applying the chemical conversion treatment to the barrier layer, the barrier layer may be subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, it becomes possible to carry out the chemical conversion treatment of the surface of the barrier layer more efficiently. In addition, by using an acid degreasing agent in which a fluorine-containing compound is dissolved in an inorganic acid for the degreasing treatment, it is possible to not only degrease the metal foil but also form a fluoride of the metal that is in a passive state, and in such a case, only the degreasing treatment may be carried out.

[0121] [Thermal adhesive resin layer 4] In the all-solid-state battery packaging material of the present disclosure, the heat-sealable resin layer 4 corresponds to the innermost layer and is a layer (sealant layer) that exhibits the function of sealing the battery element by heat-sealing the heat-sealable resin layers to each other when assembling the all-solid-state battery.

[0122] The resin constituting the heat-sealable resin layer 4 is not particularly limited as long as it is heat-sealable, but is preferably a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin. The inclusion of a polyolefin skeleton in the resin constituting the heat-sealable resin layer 4 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like. Furthermore, when the resin constituting the heat-sealable resin layer 4 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride is detected at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the peak. When the thermally adhesive resin layer 4 is a layer composed of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected by infrared spectroscopy. However, if the degree of acid modification is low, the peak becomes small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy.

[0123] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; and ethylene-butene-propylene terpolymers. Among these, polypropylene is preferred. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.

[0124] The polyolefin may be a cyclic polyolefin. The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; and cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these, cyclic alkenes are preferred, and norbornene is more preferred.

[0125] The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component. The polyolefin to be modified with an acid may be the above-mentioned polyolefin, a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a crosslinked polyolefin. The acid component used for the acid modification may be, for example, a carboxylic acid or an anhydride such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, or itaconic anhydride.

[0126] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin by replacing it with an acid component, or by block-polymerizing or graft-polymerizing an acid component to the cyclic polyolefin. The cyclic polyolefin to be acid-modified is the same as described above. The acid component used for the acid modification is the same as the acid component used for the modification of the polyolefin.

[0127] Preferred acid-modified polyolefins include polyolefins modified with a carboxylic acid or anhydride thereof, polypropylenes modified with a carboxylic acid or anhydride thereof, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.

[0128] It is also preferable that the heat-sealable resin layer 4 is formed of a polybutylene terephthalate film. The polybutylene terephthalate film may be a stretched polybutylene terephthalate film or an unstretched polybutylene terephthalate film, and is preferably an unstretched polybutylene terephthalate film. The polybutylene terephthalate film forming the heat-sealable resin layer 4 may be a polybutylene terephthalate film prepared in advance and laminated with the barrier layer 3, the adhesive layer 5, etc., to form the heat-sealable resin layer 4, or may be a film formed by melt-extruding the resin forming the polybutylene terephthalate film, and laminated with the barrier layer 3, the adhesive layer 5, etc.

[0129] The heat-sealable resin layer 4 may be formed of one type of resin alone, or may be formed of a blend polymer of two or more types of resins. Furthermore, the heat-sealable resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resins. When the heat-sealable resin layer 4 is formed of two or more layers, for example, at least one layer is formed of a polybutylene terephthalate film, and the polybutylene terephthalate film is preferably the innermost layer. When the heat-sealable resin layer 4 is formed of two or more layers, the layer not formed of a polybutylene terephthalate film may be, for example, a layer formed of a polyolefin such as polypropylene or polyethylene, or an acid-modified polyolefin such as acid-modified polypropylene or acid-modified polyethylene. When the heat-sealable resin layer 4 is formed of two or more layers, at least the layer constituting the innermost layer of the all-solid-state battery exterior material 10 among the two or more heat-sealable resin layers 4 is preferably a polybutylene terephthalate film. At least the layer in contact with adhesive layer 5 is preferably a polybutylene terephthalate film.

[0130] The heat-sealable resin layer 4 may contain a lubricant, etc., if necessary. When the heat-sealable resin layer 4 contains a lubricant, the moldability of the all-solid-state battery exterior material can be improved. The lubricant is not particularly limited, and a known lubricant can be used. The lubricant may be used alone or in combination of two or more kinds.

[0131] The lubricant is not particularly limited, but preferably includes an amide-based lubricant. Specific examples of the lubricant include those exemplified for the base layer 1. The lubricant may be used alone or in combination of two or more kinds.

[0132] When a lubricant is present on the surface of the heat-sealable resin layer 4, the amount of the lubricant is not particularly limited. However, from the viewpoint of improving the moldability of the electronic packaging material, the amount of the lubricant is preferably 10 to 50 mg / m 2 about 15 to 40 mg / m 2 The degree of

[0133] The lubricant present on the surface of the heat-fusible resin layer 4 may be a lubricant exuded from the resin constituting the heat-fusible resin layer 4, or a lubricant applied to the surface of the heat-fusible resin layer 4.

[0134] The thickness of the heat-sealable resin layer 4 is not particularly limited as long as the heat-sealable resin layers are heat-sealed to each other to exhibit the function of sealing the battery element, and may be, for example, about 100 μm or less, preferably about 85 μm or less, and more preferably about 15 to 85 μm. For example, when the thickness of the adhesive layer 5 described below is 10 μm or more, the thickness of the heat-sealable resin layer 4 is preferably about 85 μm or less, and more preferably about 15 to 45 μm. For example, when the thickness of the adhesive layer 5 described below is less than 10 μm or when the adhesive layer 5 is not provided, the thickness of the heat-sealable resin layer 4 is preferably about 20 μm or more, and more preferably about 35 to 85 μm.

[0135] [Adhesive layer 5] In the all-solid-state battery packaging material of the present disclosure, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 (or the corrosion-resistant film) and the heat-sealable resin layer 4 in order to firmly bond them together.

[0136] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The resin used to form the adhesive layer 5 may be, for example, the same adhesive as exemplified for the adhesive layer 2. The resin used to form the adhesive layer 5 preferably contains a polyolefin skeleton, and examples thereof include the polyolefin and acid-modified polyolefin exemplified for the heat-sealable resin layer 4. The inclusion of a polyolefin skeleton in the resin constituting the adhesive layer 5 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. In addition, when the resin constituting the adhesive layer 5 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride at a wave number of 1760 cm is detected. -1Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0137] From the viewpoint of firmly adhering the barrier layer 3 and the heat-fusible resin layer 4, the adhesive layer 5 preferably contains an acid-modified polyolefin. Particularly preferred examples of the acid-modified polyolefin include polyolefins modified with carboxylic acid or its anhydride, polypropylenes modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.

[0138] Furthermore, from the viewpoint of making the all-solid-state battery exterior material thin and having excellent shape stability after molding, the adhesive layer 5 is more preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. As the acid-modified polyolefin, the above-mentioned ones can be preferably exemplified.

[0139] The adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group and a compound having an epoxy group. The adhesive layer 5 is preferably at least one selected from the group consisting of polyurethane, polyester, and epoxy resin, and more preferably contains polyurethane and epoxy resin. As the polyester, for example, an amide ester resin is preferable. Amide ester resins are generally produced by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition containing at least one of these resins and the acid-modified polyolefin. In addition, if unreacted compounds such as a compound having an isocyanate group, a compound having an oxazoline group, or a curing agent such as an epoxy resin remain in the adhesive layer 5, the presence of the unreacted compounds can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.

[0140] In addition, from the viewpoint of further increasing the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C=N bond, and a COC bond. Examples of the curing agent having a heterocycle include a curing agent having an oxazoline group and a curing agent having an epoxy group. Examples of the curing agent having a C=N bond include a curing agent having an oxazoline group and a curing agent having an isocyanate group. Examples of the curing agent having a COC bond include a curing agent having an oxazoline group, a curing agent having an epoxy group, and polyurethane. It can be confirmed that the adhesive layer 5 is a cured product of a resin composition containing these curing agents by, for example, gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or other methods.

[0141] The compound having an isocyanate group is not particularly limited, but from the viewpoint of effectively increasing the adhesion between the barrier layer 3 and the adhesive layer 5, a polyfunctional isocyanate compound is preferably used. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate-based curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers. In addition, adducts, biuret products, isocyanurates, etc. are also included.

[0142] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.

[0143] The compound having an oxazoline group is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the compound having an oxazoline group include those having a polystyrene main chain and those having an acrylic main chain. In addition, examples of commercially available products include the Epocross series manufactured by Nippon Shokubai Co., Ltd.

[0144] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.

[0145] An example of a compound having an epoxy group is an epoxy resin. The epoxy resin is not particularly limited as long as it is a resin capable of forming a crosslinked structure by the epoxy group present in the molecule, and a known epoxy resin can be used. The weight average molecular weight of the epoxy resin is preferably about 50 to 2000, more preferably about 100 to 1000, and even more preferably about 200 to 800. In the present disclosure, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.

[0146] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.

[0147] The ratio of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.

[0148] The polyurethane is not particularly limited, and any known polyurethane can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing polyurethane.

[0149] The proportion of polyurethane in the resin composition constituting the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %.

[0150] In addition, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the compound having an epoxy group each function as a curing agent.

[0151] The thickness of the adhesive layer 5 is preferably about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, or about 5 μm or less, and is preferably about 0.1 μm or more, or about 0.5 μm or more, and the thickness range is preferably about 0.1 to 50 μm, about 0.1 to 40 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 to 5 μm, about 0.5 to 50 μm, about 0.5 to 40 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, or about 0.5 to 5 μm. More specifically, in the case of the adhesive exemplified in the adhesive layer 2 or a cured product of an acid-modified polyolefin and a curing agent, the thickness is preferably about 1 to 10 μm, more preferably about 1 to 5 μm. When a resin exemplified for the heat-fusible resin layer 4 is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. When the adhesive layer 5 is an adhesive exemplified for the adhesive layer 2 or a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed, for example, by applying the resin composition and curing it by heating or the like. When a resin exemplified for the heat-fusible resin layer 4 is used, the adhesive layer 5 can be formed, for example, by extrusion molding the heat-fusible resin layer 4 and the adhesive layer 5.

[0152] [Surface coating layer] The exterior material of the present disclosure may have a surface coating layer on the substrate layer 1 (the side of the substrate layer 1 opposite to the barrier layer 3) as necessary, for the purpose of improving at least one of design, scratch resistance, formability, etc. The surface coating layer is a layer located on the outermost layer side of the exterior material when an all-solid-state battery is assembled using the exterior material.

[0153] The surface coating layer can be formed from a resin such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, or epoxy resin.

[0154] When the resin forming the surface coating layer is a curable resin, the resin may be either a one-component curable type or a two-component curable type, but is preferably a two-component curable type. Examples of two-component curable resins include two-component curable polyurethane, two-component curable polyester, and two-component curable epoxy resin. Among these, two-component curable polyurethane is preferred.

[0155] Examples of two-component curing polyurethane include polyurethanes containing a base material containing a polyol compound and a curing agent containing an isocyanate compound.Preferably, two-component curing polyurethanes are used in which a polyol such as polyester polyol, polyether polyol, and acrylic polyol is used as a base material, and an aromatic or aliphatic polyisocyanate is used as a curing agent.In addition, as the polyol compound, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the hydroxyl group at the end of the repeating unit.

[0156] The surface coating layer may contain additives such as the above-mentioned lubricant, antiblocking agent, matting agent, flame retardant, antioxidant, tackifier, and antistatic agent in at least one of the surface and the inside of the surface coating layer, as necessary, depending on the functionality to be provided to the surface of the surface coating layer. Examples of the additives include fine particles having an average particle size of about 0.5 nm to 5 μm. The average particle size of the additive is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.

[0157] The additive may be either inorganic or organic. The shape of the additive is not particularly limited, and examples of the shape include spherical, fibrous, plate-like, amorphous, and scaly.

[0158] Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, acrylate resin, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. The additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoint of dispersion stability and cost. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.

[0159] The method for forming the surface coating layer is not particularly limited, and examples thereof include a method of applying a resin for forming the surface coating layer. When an additive is blended in the surface coating layer, a resin mixed with the additive may be applied.

[0160] The thickness of the surface coating layer is not particularly limited as long as it exhibits the above-mentioned functions as a surface coating layer, and may be, for example, about 0.5 to 10 μm, and preferably about 1 to 5 μm.

[0161] The method for producing the all-solid-state battery exterior material is not particularly limited as long as a laminate in which each layer included in the all-solid-state battery exterior material of the present disclosure is laminated can be obtained, and an example of the method includes a method including a step of laminating at least a base layer 1, a barrier layer 3, and a heat-sealable resin layer 4 in this order from the outside.

[0162] An example of the manufacturing method of the all-solid-state battery exterior material of the present disclosure is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used for forming the adhesive layer 2 is applied to the base layer 1 or to the barrier layer 3, the surface of which has been subjected to chemical conversion treatment as necessary, by a coating method such as gravure coating or roll coating, and then dried, and the barrier layer 3 or base layer 1 is laminated thereon, and the adhesive layer 2 is cured.

[0163] Next, a thermally adhesive resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the thermally adhesive resin layer 4 is directly laminated on the barrier layer 3, the resin component constituting the thermally adhesive resin layer 4 may be applied onto the barrier layer 3 of the laminate A by a method such as gravure coating or roll coating. In addition, in the case of providing the adhesive layer 5 between the barrier layer 3 and the heat-sealable resin layer 4, for example, there can be mentioned (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 on the barrier layer 3 of the laminate A by co-extruding them (co-extrusion lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated, and laminating this on the barrier layer 3 of the laminate A by a thermal lamination method, (3) a method of laminating an adhesive for forming the adhesive layer 5 on the barrier layer 3 of the laminate A by an extrusion method or a solution coating, drying at a high temperature, and further baking, and laminating the heat-sealable resin layer 4, which has been formed in advance into a sheet-like film, on this adhesive layer 5 by a thermal lamination method, and (4) a method of laminating the laminate A and the heat-sealable resin layer 4 via the adhesive layer 5 while pouring a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-sealable resin layer 4, which has been formed in advance into a sheet-like film (sandwich lamination method), and the like.

[0164] When a surface coating layer is provided, the surface coating layer is laminated on the surface of the base layer 1 opposite to the barrier layer 3. The surface coating layer can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer to the surface of the base layer 1. The order of the step of laminating the barrier layer 3 on the surface of the base layer 1 and the step of laminating the surface coating layer on the surface of the base layer 1 is not particularly limited. For example, after forming the surface coating layer on the surface of the base layer 1, the barrier layer 3 may be formed on the surface of the base layer 1 opposite to the surface coating layer.

[0165] As described above, a laminate including the optional surface coating layer / substrate layer 1 / optional adhesive layer 2 / optional corrosion-resistant film / barrier layer 3 / optional corrosion-resistant film / optional adhesive layer 5 / thermal adhesive resin layer 4 in this order is formed, and in order to strengthen the adhesion of the optional adhesive layer 2 and adhesive layer 5, the laminate may be subjected to a heat treatment such as a hot roll contact type, hot air type, near infrared type, or far infrared type. Examples of the conditions for such a heat treatment include about 150 to 250° C. for about 1 to 5 minutes.

[0166] The buffer layer 6 may be laminated on the outer side (barrier layer 3 side) of the thermally adhesive resin layer 4. Therefore, the buffer layer 6 may be laminated in the lamination step according to the position to be laminated. For example, in the case of producing an exterior material 10 having the buffer layer 6, adhesive layer 2, base material layer 1, adhesive layer 2, barrier layer 3, adhesive layer 5, and thermally adhesive resin layer 4 in this order, for example, the base material layer 1 may be laminated on one side of the barrier layer 3 via the adhesive layer 2, the buffer layer 6 may be laminated on the base material layer 1 via the adhesive layer 2, and the adhesive layer 5 and the thermally adhesive resin layer 4 may be laminated on the other side of the barrier layer 3 to produce the exterior material 10.

[0167] In the all-solid-state battery packaging material, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, in order to improve or stabilize film-forming properties, lamination processing, suitability for secondary processing of final products (pouching, embossing), etc. For example, by subjecting at least one surface of the base layer 1 to corona treatment, it is possible to improve or stabilize film-forming properties, lamination processing, suitability for secondary processing of final products, etc. Furthermore, for example, by subjecting the surface of the base layer 1 opposite to the barrier layer 3, it is possible to improve the printability of ink on the surface of the base layer 1. EXAMPLES

[0168] The present disclosure will be described in detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the examples.

[0169] <Exterior material manufacturing> [Example 1] A biaxially oriented nylon film (thickness 15 μm) was prepared as a substrate layer. Next, a barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm, with a corrosion-resistant coating using chromic acid formed on both sides) was laminated on the substrate layer by a dry lamination method. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film were laminated to prepare a substrate layer / adhesive layer / barrier layer laminate. Next, a nonwoven fabric (polyethylene terephthalate fiber with a fiber diameter of 10 μm, thickness 2600 μm, basis weight 120 g / m) was laminated on the substrate layer of this laminate as a buffer layer. 2) was laminated by the dry lamination method. The adhesive used for adhesion between the base layer and the buffer layer by the dry lamination method was a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound), and the thickness after curing was set to 3 μm. The obtained laminate was subjected to an aging treatment. Next, on the barrier layer of this laminate, maleic anhydride-modified polypropylene (thickness 40 μm) as an adhesive layer and polypropylene (thickness 40 μm) as a heat-sealable resin layer were co-extruded, so that an adhesive layer / heat-sealable resin layer was laminated on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material in which the buffer layer (2600 μm) / adhesive layer (3 μm) / base layer (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / heat-sealable resin layer (40 μm) were laminated in this order.

[0170] [Example 2] A biaxially oriented nylon film (thickness 15 μm) was prepared as a substrate layer. Next, a barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm, with a corrosion-resistant coating using chromic acid formed on both sides) was laminated on the substrate layer by a dry lamination method. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film were laminated to prepare a substrate layer / adhesive layer / barrier layer laminate. Next, a silicone rubber sheet (thickness 1 mm, rubber hardness 50) was laminated as a buffer layer on the substrate layer of this laminate by a dry lamination method. The adhesive used for adhesion between the base layer and the buffer layer by the dry lamination method was a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound), and the thickness after curing was 3 μm. The obtained laminate was subjected to an aging treatment. Next, on the barrier layer of this laminate, maleic anhydride-modified polypropylene (thickness 40 μm) as an adhesive layer and polypropylene (thickness 40 μm) as a heat-sealable resin layer were co-extruded to laminate an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material in which the buffer layer (1 mm) / adhesive layer (3 μm) / base layer (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / heat-sealable resin layer (40 μm) were laminated in this order.

[0171] [Example 3] A biaxially oriented nylon film (thickness 15 μm) was prepared as a substrate layer. Next, a barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm, with a corrosion-resistant coating using chromic acid formed on both sides) was laminated on the substrate layer by a dry lamination method. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil to form an adhesive layer (thickness 3 μm after curing) on ​​the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film were laminated to prepare a substrate layer / adhesive layer / barrier layer laminate. Next, a nonwoven fabric (polyethylene terephthalate fiber with a fiber diameter of 10 μm, thickness 160 μm, basis weight 30 g / m) was laminated on the substrate layer of this laminate as a buffer layer. 2 ) was laminated by the dry lamination method. The adhesive used for adhesion between the base layer and the buffer layer by the dry lamination method was a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound), and the thickness after curing was set to 3 μm. The obtained laminate was subjected to an aging treatment. Next, on the barrier layer of this laminate, maleic anhydride-modified polypropylene (thickness 40 μm) as an adhesive layer and polypropylene (thickness 40 μm) as a heat-sealable resin layer were co-extruded, so that an adhesive layer / heat-sealable resin layer was laminated on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material in which the buffer layer (160 μm) / adhesive layer (3 μm) / base layer (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / heat-sealable resin layer (40 μm) were laminated in this order.

[0172] [Comparative Example 1] An exterior material was obtained in the same manner as in Example 1, except that the buffer layer and the adhesive layer thereunder were not provided, in which a base material layer (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / thermally adhesive resin layer (40 μm) were laminated in this order.

[0173] <Manufacturing of all-solid-state batteries> Using the exterior materials 10 obtained in Example 1 and Comparative Example 1, all-solid-state batteries 70 as shown in the schematic diagram of Fig. 1 were fabricated. Specifically, in a vacuum environment, a positive electrode layer 30 in which LiCoO2 was laminated as a positive electrode active material layer 31 (thickness 100 µm) on an aluminum alloy foil as a positive electrode current collector 32 (thickness 20 µm), and a negative electrode layer 20 in which graphite was laminated as a negative electrode active material layer 21 (thickness 100 µm) on a SUS304 foil as a negative electrode current collector 22 (thickness 30 µm) were laminated via a solid electrolyte layer 40 (Li2S:P2S5 = 70:30 mass%, thickness 100 µm) to fabricate a single cell 50. When the all-solid-state battery is viewed from above, the positive electrode active material layer 31 is 25 mm long x 25 mm wide, the positive electrode current collector 32 is 50 mm long x 30 mm wide, the negative electrode active material layer 21 is 30 mm long x 30 mm wide, the negative electrode current collector 22 is 50 mm long x 30 mm wide, and the solid electrolyte layer is 30 mm long x 30 mm wide. Next, a terminal 60 was joined to each of the positive electrode current collector 32 and the negative electrode current collector 22.

[0174] Next, two sheets of the above-mentioned exterior material (40 mm long × 40 mm wide) were prepared. Next, the heat-sealable resin layers of the two exterior materials were placed opposite each other, and the unit cell 50 was sandwiched between them from above and below, and the periphery of the exterior materials was heat-sealed to produce each all-solid-state battery in a vacuum environment.

[0175] <Evaluation of uniformity of high pressure press> The uniformity of the high pressure press on the press surface of the exterior material obtained above was evaluated as follows. First, two exterior materials (60 mm long x 60 mm wide) were prepared for each of Examples 1 to 3 and Comparative Example 1. The first exterior material was placed on a horizontal surface with the heat-sealable resin layer facing up, and an aluminum block (50 mm long x 50 mm wide) was placed on top of it. A press scale (Fujifilm pressure image analysis system FPD-9210) was placed on top of it, and a second exterior material was placed on top of it with the heat-sealable resin layer facing down. In this state, the exterior material was pressed from above and below with a pressure of 100 MPa (high pressure pressing with stainless steel plates from above and below), and the press was released after 1 hour, and the pressure distribution applied to the exterior material was evaluated with the press scale. The uniformity of the high pressure press was evaluated using the pressure image analysis system FPD-9210. If the pressure difference between the center (5 mm square area) and the peripheral area was less than ±10%, it was rated A, if it was between ±20% and ±10%, it was rated B, and if it was more than ±30%, it was rated C. The results are shown in Table 1.

[0176] [Table 1]

[0177] As described above, the present disclosure provides the following aspects of the invention. Item 1. An exterior material for an all-solid-state battery, comprising a laminate having, from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, The laminate has a layer having a buffer function on an outer side of the thermally adhesive resin layer. Item 2. The exterior material for an all-solid-state battery according to Item 1, wherein the layer having a buffer function is provided outside the barrier layer. Item 3. The exterior material for an all-solid-state battery according to Item 1 or 2, wherein the layer having a buffer function is made of rubber or nonwoven fabric. Item 4. The exterior material for an all-solid-state battery according to any one of Items 1 to 3, wherein the base material layer constitutes the layer having the buffer function. Item 5. An all-solid-state battery, comprising: a battery element including at least a unit cell including a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer laminated between the positive electrode active material layer and the negative electrode active material layer; the battery element being housed in a packaging body formed of an exterior material for all-solid-state batteries; The all-solid-state battery exterior material is composed of a laminate having, from the outside, a base layer, a barrier layer, and a heat-sealable resin layer in this order, The laminate has a layer having a buffer function on an outer side of the thermally adhesive resin layer. Item 6. The method includes a step of laminating, from the outside, a base layer, a barrier layer, and a heat-sealable resin layer in this order to obtain a laminate, The laminate has a layer having a buffer function on an outer side of the thermally adhesive resin layer. [Explanation of symbols]

[0178] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer 6 Buffer layer 10 Exterior material for all-solid-state batteries 11 Press surface 20 Negative electrode layer 21 Negative electrode active material layer 22 Negative electrode current collector 30 Positive electrode layer 31 Cathode active material layer 32 Positive electrode current collector 40 Solid electrolyte layer 50 D cell 60 Terminals 70 All-solid-state battery

Claims

1. An exterior material for an all-solid-state battery, comprising a laminate including at least a base layer, a barrier layer, and a heat-sealable resin layer in this order from the outside, the laminate has a layer having a buffer function only on the outer side of the barrier layer, The material constituting the layer having a buffer function is rubber, a nonwoven fabric, or a foam sheet.

2. The exterior material for an all-solid-state battery according to claim 1 , wherein the layer having a buffer function is provided outside the base material layer.

3. The exterior material for an all-solid-state battery as described in claim 1, wherein the base material layer constitutes a layer having the buffer function.

4. The exterior material for an all-solid-state battery according to any one of claims 1 to 3, wherein a material constituting the layer having a buffer function is rubber or a nonwoven fabric.

5. An all-solid-state battery, comprising: a battery element including at least a unit cell including a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer laminated between the positive electrode active material layer and the negative electrode active material layer, the battery element being accommodated in a packaging body formed of an exterior material for an all-solid-state battery; The all-solid-state battery exterior material is composed of a laminate having, from the outside, a base layer, a barrier layer, and a heat-sealable resin layer in this order, the laminate has a layer having a buffer function only on the outer side of the barrier layer, The material constituting the layer having a buffer function is rubber, a nonwoven fabric, or a foam sheet.

6. The method includes a step of laminating, from the outside, a base layer, a barrier layer, and a heat-sealable resin layer in this order to obtain a laminate, the laminate has a layer having a buffer function only on the outer side of the barrier layer, The method for producing an exterior material for an all-solid-state battery, wherein a material constituting the layer having a buffer function is rubber, a nonwoven fabric, or a foam sheet.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2001297737A

  • Wrapper

    JP2004091024A

  • Manufacturing method of non-aqueous electrolyte battery

    JP2008257922A

  • Non-aqueous electrolyte battery and manufacturing method for producing the same

    JP2009176513A

  • Method for manufacturing electrode body, and method for manufacturing battery

    JP2012142228A